Reporting both length and mass values to quantify body size for amphibians and reptiles - Liang, Tao (Zootaxa, 2022)
Body size is perhaps the most important trait for organism biologists, as it is associated with a myriad of ecological, evolutionary, behavioral, morphological, physiological and life-history aspects (e.g., rates of molecular evolution, metabolic rates, predation, reproduction), and with extinction risk. There are, however, several measures commonly used to quantify organism body size. Within ectothermic tetrapods, the most common measures include snout-vent length (SVL, mostly in lizards), and total length (TL, in most snakes). In endotherms, however, and especially in mammals, body mass is the most common measure of size.